Las elecciones de febrero de 1936 en la provincia de León - Martínez Celada, José Luis (Estudios humanísticos. Geografía, historia y arte, 1998)
The february 1936 parliamentary elections in Spain involved the definitive settlement of a social division incited by political ideas close to the Civil War. The province of León had taken an active role in the previous revolutionary months, whose first consecuencies were the capture of many workers and miners. Thus, the amnisty for them would be the crucial question in order to get popular support for one of the biggest electoral blocs. The count in this province gave the victory to the right-wings, although the left tendencies had a never known support, crowing their expectatives in all over León.